2016
DOI: 10.18632/oncotarget.9100
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between insulin-like growth factor axis gene polymorphisms and clinical outcome in advanced gastric cancer patients treated with FOLFOX

Abstract: The insulin-like growth factor (IGF) axis plays a crucial role in proliferation, differentiation, migration, angiogenesis, and apoptosis. The present study evaluated the associations between IGF axis single-nucleotide polymorphisms (SNPs) and clinical outcomes in advanced gastric cancer (AGC) patients treated with oxaliplatin, 5-fluorouracil, and leucovorin (FOLFOX). A total of 190 patients undergoing FOLFOX chemotherapy for AGC were considered eligible for this study. Forty-four SNPs of 10 IGF axis genes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…6 Gallagher et al 7 have reported that patients with Laron syndrome have a decreased susceptibility of developing cancer. 17 Insulin-like growth factor 2 mRNA-binding protein 2 (IGF2BP2) is encoded by the IGF2BP2 gene and acts as an RNA-binding protein of IGF2 mRNA. 8 Recently, some case-control studies have focused on the relationship of IGFBP3 and IGF1 single nucleotide polymorphisms (SNPs) with the risk of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…6 Gallagher et al 7 have reported that patients with Laron syndrome have a decreased susceptibility of developing cancer. 17 Insulin-like growth factor 2 mRNA-binding protein 2 (IGF2BP2) is encoded by the IGF2BP2 gene and acts as an RNA-binding protein of IGF2 mRNA. 8 Recently, some case-control studies have focused on the relationship of IGFBP3 and IGF1 single nucleotide polymorphisms (SNPs) with the risk of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This SNP includes rs6214, rs6220, rs35767, and rs5742612. It is reported that the substitution of G to C at the rs5742612 site leads to an increase in plasma IGF1 levels, which increases the risk of the malignant tumor ( 20 ). Since rs5742612 has a relatively small frequency of about 10–40% in the population included in the third phase of the Human 1000 Genome Project, so this study pays special attention to rs5742612 ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…BCL2 is a well-known anti-apoptosis gene in multiple cancers [ 37 , 38 ]. The IGF axis-pathway SNPs can influence FOLFOX chemotherapy in patients with advanced gastric cancer [ 39 ]. Secreted VEGFC can enhance gastric cancer cell invasion and conferred cisplatin resistance to Rho GDP dissociation inhibitor 2 (RhoGDI2)-overexpressing cells [ 40 ].…”
Section: Discussionmentioning
confidence: 99%